Dimensiones Y Estilos De Liderazgo Desde La Percepción De La Gerencia Y El Trabajador - JESUS MARMOLEJO RODRIGUEZ (2017)
Dimensiones Y Estilos De Liderazgo Desde La Percepción De La Gerencia Y El Trabajador